Dataset on the questionnaire-based survey of the readiness of government accountants to implement international public sector accounting standards (IPSAS)Mendeley Data - Moawiah Awad Alghizzawi (Data in Brief)
This article presents a data set concerning the effect of human resource and information technology on the readiness of government accountants to implement IPSAS. The data was collected by a face-to-face survey with a questionnaire using five point Likert scale. The survey sample involved 331 government accountants in Jordan. The questionnaire consists of three sections. Section A addresses the demographic attributes of the respondents. Section B contains 2 parts; part (1) measures human resource, part (2) measures information technology. Section C measures the readiness of government accountants to implement IPSAS. Each section contains seven to eight statements with a 1-5 Likert scale in order to assess respondents’ level of agreement or disagreement. The detailed data set is accompanied by the original questionnaire in English and Arabic. The data set is providing a valuable tool to understand the contributions of human resource and information technology in achieving the readiness to implement IPSAS, develop hypotheses and design a questionnaire survey.